Design of a cable-driven snake-arm robot - Cai, Lirong (2009)
In recent years, much research has been done on the snake-arm robot due to its wide range of potential applications. The main advantage of a snake-arm robot is the ability to access restricted spaces beyond the reach of existing robots. As such, snake-arm robots can do tasks which have limited access.